Value of cardiac 123I-mIBG scintigraphy in prognosis of catheter ablation outcome in patients with atrial fibrillation. (20th July 2021) - Sazonova, S; Varlamova, JV; Nikitin, NA; Minin, SM; Kisteneva, IV; Batalov, RE; Mishkina, AI; Ilushenkova, JN; Zavadovsky, KV; Popov, SV; Romanov, AB
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Russian Science Foundation Background. Previous studies show inconsistent results on the role of innervation imaging (with 123I-mIBG) in predicting late atrial fibrillation (AF) recurrence after catheter ablation (CA). These studies included patients with paroxysmal  AF and studied prognostic value of post CA I-123-mIBG parameters. Current study investigated the ability of pre CA 123-I-mIBG imaging to predict late AF recurrence in patients with persistent AF. Thus, the goal of the present study was to estimate the utility of pre-procedural cardiac 123I-mIBG scintigraphy to identify patients at risk for AF recurrence after CA. Methods. 123I-mIBG cardiac imaging was performed before CA in 82 patients with persistent AF. Patients were followed for 12 months. A blanking period of 3 months was applied. The primary endpoint of the study was AF recurrence between 3 and 12 months after ablation. Results. Multivariable analysis demonstrated that late heart-to-mediastinum ratio (H/Mlate) and washout rate (WR) were independent predictors of AF recurrence. ROC-curve analysis data showed that H/Mlate <1.6 (sensitivity 73.53 %, specificity 81.3%, AUC  0, 792, p < 0.001) and  WR > 25, 11 (sensitivity 70.6%, specificity 70.8.3%, AUC  0, 712, p < 0.001) indicate high probability of AF relapses during 12 months after CA. Kaplan-Meier analysis showed that the H/Mlate < 1.6, WR > 25, 11 and LAD > 45 mm  significantly increase the risk of AF recurrence after CA (p < 0.001, p < 0.001, p < 0.025 respectively). Conclusion. Pre CA parameters of global cardiac sympathetic activity estimated by 123I-mIBG scintigraphy are associated with late AF relapses in persistent AF patients.